Mathematical Prediction for BFRP Retrofitted after Fatigue Loading of Concrete Specimens - Anandakumar, R.; Ravikumar, M.S.; Selvamony, C. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
This paper deals with the experiment investigations on the Basalt Fibre Reinforced Polymer composites wrapped concrete specimens for determining the mathematical prediction for retrofitting of concrete specimens. For the past three decades, fibres are being effectively utilized in engineering fields. Some countries do not have specified codes for structural designing of Fibre Reinforced Polymer composites. Especially for this situation, the mathematical predictions were determined by experimentally for Basalt Fibre Reinforced Polymer composites retrofitted concrete. For this experiment, cubes, cylinders and prisms were cast using M30 grade concrete to analyze the characteristic strengths. The tests were carried out with and without Basalt Fibre Reinforced Polymer wrapping and retrofitted after 0%, 30%, 60% and 90% fatigue loaded or preloaded specimens. The retrofitted specimens with Basalt Fibre Reinforced Polymer wrapping, even after 90% fatigue loaded possess higher strength than conventional one. The observed readings were analyzed and mathematical prediction was developed by using readings and graphical representations. From the study, similar results were observed through experiments and mathematical predictions.